MORAL HARASSEMENT IN CONGOLESE LABOUR LAW - Éric, LEKIE YOKA (IJRDO - Journal of Social Science and Humanities Research, 2024)
Moral harassment is a phenomenon that affects many workers around the world. In the Democratic Republic of Congo (DRC), this scourge is also present in both public and private companies. In this dissertation, we expose the different types of moral harassment and the treatment reserved for it by the Congolese legislator, which we have analyzed with the greatest attention. Several books and articles have been written on moral harassment, shedding light on the various forms of moral harassment, the consequences of these behaviors on workers, and the means of prevention around the world, particularly in the Democratic Republic of Congo.